The effects of academic qualifications, expertise and subject matter knowledge of literary devices amongst Malaysian ESL teachers / Manickavasagar Govindasamy - Manickavasagar , Govindasamy (2017)

(untitled)
The Literature Component is a tested section of the English language paper at secondary school level since 2000 and much research has been conducted on English language teachers who are involved in teaching the component. This research investigates the effects of academic qualifications and expertise of English language teachers on their subject matter knowledge of literary devices. This research is based on the Objective Knowledge Growth Framework based on Popper’s theory that guides the growth of professional knowledge. The objective of this research was to investigate empirically the effects of academic qualification, expertise and subject matter knowledge of literary devices among Malaysian English language teachers. The research questions were categorized according to the above objective. The first research question dealt with the influences of academic qualifications and expertise of English language teachers on their subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. The hypothesis was to show there was no significant influence on the subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices among English language teachers based on their academic qualifications and expertise. The second research question was to determine if there were differences in the subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices between English major and non-English major, TESL and non-TESL and KPLI and non-KPLI English language teachers. The hypothesis was to show there was no difference in the subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices between English major and non- English major, TESL and non-TESL and KPLI and non-KPLI English language teachers. The third research question was to determine the extent of correlation between subject matter knowledge of literary devices and familiarity with the use of literary devices, subject matter knowledge of literary devices and understanding of the functions of literary devices and familiarity with the use of literary devices and understanding of the functions of literary devices among English language teachers. Hypothesis was to show there was no correlation between subject matter knowledge of literary devices and familiarity with the use of literary devices, subject matter knowledge of literary devices and understanding of the functions of literary devices, and familiarity with the use of literary devices and understanding of the functions of literary devices among English language teachers. The fourth research question attempted to discover whether there were interactive effects of academic qualifications and expertise of English language teachers on subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. The hypothesis was to show that there was no interactive effects of academic qualifications and expertise of English language teachers on their subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. A mixed method approach was used in this research in which quantitative data was collected from questionnaires and worksheets while qualitative data was obtained from interviews. For the first research question the statistical method used was the One-way ANOVA. If there were significant differences among the groups in academic qualifications and expertise, then the Scheffe post hoc multiple comparison test was used to indicate which groups were influenced by academic qualifications and expertise of English language teachers. The statistical test used for the second research question was the Independent t-test that would indicate the influences of subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices between English major and non- English major, TESL and non-TESL and KPLI and non-KPLI English language teachers. For the third research question, the Pearson Correlation would inform the extent of correlation and the Coefficient of Determination would indicate the percentage of overlapping between subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. The fourth research question was analysed using the two-way ANOVA. Based on the graphs if there were interactions, then the two-way ANOVA was used to determine the significant differences in academic qualifications and expertise in subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. If significant differences existed, then the Turkey multiple comparisons test was used to determine which groups were significantly different. The first major finding revealed that academic qualifications and expertise of English language teachers influenced their subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. The null hypothesis was rejected as academic qualifications and expertise of English language teachers had influenced their subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. The second major finding indicated that there were differences between the English major and the non-English major, the TESL and the non-TESL and KPLI and the non- non-English language teachers in their subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. The null hypothesis was rejected as there were differences between English major and the non-English major, the TESL and the non-TESL and KPLI and the non- non-English language teachers in their subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. Another finding of this research revealed there was high positive correlation between subject matter knowledge of literary devices and familiarity with the use of literary devices, subject matter knowledge of literary and understanding of the functions of literary devices and familiarity with the use of literary devices and understanding of the functions of literary devices among English language teachers. However, the correlation of determination indicated there was only 50% overlapping between subject matter knowledge of literary devices and familiarity with the use of literary devices, subject matter knowledge of literary and understanding of the functions of literary devices and familiarity with the use of literary devices and understanding of the functions of literary devices among English language teachers. The null hypothesis was rejected as there was positive was high positive correlation between subject matter knowledge of literary devices and familiarity with the use of literary devices, subject matter knowledge of literary and understanding of the functions of literary devices and familiarity with the use of literary devices and understanding of the functions of literary devices among English language teachers. The other notable findings of this research revealed there were interactions between the academic qualifications and expertise of English language teachers on subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. This study aims to provide useful insight into the different aspects of the effects of subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices among English language teachers who are presently involved in teaching the literary component. The understanding of how language works among language teachers would assist them to develop their competency in literary analysis and the systematic awareness of the general organization of language in literary texts. This form of objective knowledge growth can remove their false perceptions and ideas related to literary analysis. The use of literary devices which is a form of language oriented analysis can provide the ‘why’ and ‘how’ to explain the literary texts among English language teachers. This language based approach can assist English language teachers with a “way-in” to the different genres in the literature component and provide an objective analysis that is less impressionistic. A clear empirical evidence of the subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices among English language teachers based on their academic qualifications and expertise will reveal explicit information on the needs of those who are directly involved in the teaching of the literature component. From the evidence they can understand the importance of literary devices that is predominantly concerned with textual analysis in which the primary focus is assigned to language. The findings of the study can enlighten the relevant authorities like the Ministry of Education (Malaysia), Teacher Education Division (Malaysia) and higher institutions of education as to what needs to be reviewed in the objectives of the literature component to ensure that it is more current and in accordance with the demands of the language policy in Malaysia. Subsequently, new literature programmes (teaching files, worksheets and modules) can be developed based on literary devices as a new approach in the teaching of the literature component. Among the implications of this study is that future English language teachers should be equipped with sufficient subject matter knowledge of literary devices, familiarity with the use of literary devices and understanding of the functions of literary devices. This form of literary knowledge enrichment can be beneficial to English language teachers to approach the literature component with confidence from the language perspectives which is one of its objectives.